Photoprotection of PSI by Far-Red Light Against the Fluctuating Light-Induced Photoinhibition in Arabidopsis thaliana and Field-Grown Plants. (23rd January 2017) - Kono, Masaru; Yamori, Wataru; Suzuki, Yoshihiro; Terashima, Ichiro
Abstract : It has been reported that PSI photoinhibition is induced even in wild-type plants of Arabidopsis thaliana, rice and other species by exposure of leaves to fluctuating light (FL) for a few hours. Because plants are exposed to FL in nature, they must possess protective mechanisms against the FL-induced photodamage. Here, using A. thaliana grown at various irradiances, we examined PSI photoprotection by far-red (FR) light at intensities comparable with those observed in nature. Dark-treated leaves were illuminated by red FL alternating high/low light at 1, 200/30 µmol m −2 s −1 for 800 ms/10 s. By this FL treatment without FR light for 120 min, the level of photo-oxidizable P700 was decreased by 30% even in the plants grown at high irradiances. The addition of continuous FR light during the FL suppressed this damage almost completely. With FR light, P700 was kept in a more oxidized state in both low- and high-light phases. The protective effect of FR light was diminished more in mutants of the NADH dehydrogenase-like complex (NDH)-mediated cyclic electron flow around PSI (CEF-PSI) than in the PGR5 (proton gradient regulation 5)-mediated CEF-PSI, indicating that the NDH-mediated CEF-PSI would be a major contributor to PSI photoprotection in the presence of FR light. We also confirmed that PSI photoinhibition decreased with the increase in growth irradiance in A. thaliana and field-grown plants, and that this PSI photodamage was largely suppressed by addition of FR light. These results clearly indicate that the most effective PSI protection is realized in the presence of FR light.